What is reality in law? Refutation of some elementary ideas of legal realism and reaffirmation of normativism - Ortega Monge, Guillermo (2026)
Legal realistics think that normativism is wrong beacause it does not behave according towhat they call reality. This article affirms that the subject matter of law is a literary creation, thus, unnafiliatted with reality. From there, the study intends to refute some elementary ideas of legal realism and to propitiate a reconstruction of normativism.